Centrifugal particulate matter separation device for waste gas treatment - AN JINSHENG (2023)
The invention provides a centrifugal particulate matter separation device for waste gas treatment, and relates to the technical field of waste gas treatment, the centrifugal particulate matter separation device comprises a base and a collection cylinder; the base adopts a rectangular plate structure; a mounting frame is arranged on the rear side of the top of the base; the collecting barrel is of a cylindrical structure with the hollow interior. The collecting barrel further comprises an ejector block, a first connecting rod and a second connecting rod. The ejector block is of a wedge-shaped block structure. The sliding plate is of a circular-plate-shaped structure, the sliding plate is arranged in the collecting cylinder in a sliding mode, and the outer wall of the sliding plate is attached to the inner wall of the collecting cylinder; compared with a traditional waste gas particulate matter separation device, the waste gas particulate matter separation device can reduce the occupied space of dust particles,